(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
The joint contents of the transmission of the disease pathogens from dead bacilli-carrier to the healthy caterpillar was studied. Due to the experimental results, it is determined that the caterpillars of Brown Tail Moth are not susceptible towards the influence of secondary infection both under the common laboratory conditions and under high air humidity.